Reply to 'comment on 'Braneworld remarks in Riemann-Cartan manifolds'' - Hoff da Silva, J. M. [UNESP]; da Rocha, R. (Iop Publishing Ltd, 2009)
In this brief reply, we elucidate some missing points in the comment (Khakshournia S 2009 Class. Quantum Grav. 26 178001) on our original paper (Hoff da Silva J M and da Rocha R 2009 Class. Quantum Grav. 26 055007), explicitly showing that the comment is unfounded in this context. We show that the term proposed equals zero, since the brane discontinuity is correctly defined in the torsion.